The Digital Leadership, Teamwork, Work Environment, Competencies and Employee Performance: Assessing the Superior Facility in Manufacturing Context - Lebrata, Lebrata; Isramilda, Isramilda; Rumengan, Angelina Eleonora; Satriawan, Bambang (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2024)
This study aims to analyze the factors that influence employee performance in manufacturing companies in Batam City. With a focus on digital leadership, teamwork, work environment, and human resource competencies, this study also explores the impact of management system integration (ISO 9001, 14000, and 45001) on work motivation and job satisfaction. Survey and path analysis methods were used to collect and analyze data from 212 respondents. The results show that a positive work environment, effective teamwork, and good human resource competencies contribute significantly to employee performance. The implications of this study provide valuable insights for companies in improving their employees' performance and satisfaction.